2012
DOI: 10.1186/1472-6882-12-243
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of Gleditsia sinensis thorn suppresses angiogenesis in vitro and in vivo

Abstract: BackgroundGleditsia sinensis thorns have been widely used in traditional Korean medicine for the treatment of several diseases, including obesity, thrombosis, and tumor-related diseases. The aim of the study is to determine the antiangiogenic effect of Gleditsia sinensis thorns in vitro and in vivo in a bid to evaluate its potential as an anticancer drug.MethodsEthanol extract of Gleditsia sinensis thorns (EEGS) were prepared and used for in vitro and in vivo assays. In vitro antiangiogenic effect of EEGS was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…19) In the present study, we attempted to identify the active constituents of EEGS that display these cytostatic and anti-angiogenic properties. Unexpectedly, activityguided fractionation and spectral studies identified cytochalasin H, a fungal secondary metabolite, as an active constituent of G. sinensis thorns.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…19) In the present study, we attempted to identify the active constituents of EEGS that display these cytostatic and anti-angiogenic properties. Unexpectedly, activityguided fractionation and spectral studies identified cytochalasin H, a fungal secondary metabolite, as an active constituent of G. sinensis thorns.…”
Section: Discussionmentioning
confidence: 99%
“…19) EEGS efficiently inhibited cellular mobility and 3-dimensional vascular tube formation by HUVEC primary cells, which led to the suppression of vessel formation in the matrigels that had been premixed with pro-angiogenic proteins and implanted in nude mice. In the present study, we tested the in vitro anti-angiogenic potential of G. sinensis thorns which had been purchased from 5 different herbal plant suppliers.…”
Section: Anti-angiogenic Potential Of Eegsmentioning
confidence: 99%
See 3 more Smart Citations